ANALISIS SALURAN PEMASARAN PERTANIAN DAN CABAI MERAH DI DESA PAKULI KECAMATAN KAPONTORI KABUPATEN BUTON - Wardana, Wardana (Media Agribisnis, 2017)
The purpose of this study was (1) to determine the costs and income of red pepper farming in Wakuli Village, Kapontori Sub-district, Buton Regency; (2) to find out the feasibility value of red pepper farming in Wakuli Village, Kapontori Sub-district, Buton Regency and to find out the marketing channel of red pepper in Wakuli Village, Kapontori Sub-district, Buton Regency. This research was carried out in Wakuli Village, Kapontori Sub-district, Buton Regency, from August to September 2016. The sample of farmers was 20 people; the sample consisted of 3 village collectors, 1 large wholesaler and 4 retailers. The analysis used is income analysis. Quantitative data is tabulated and configured in the same unit. Farming income is the difference between revenue and all costs incurred. Red pepper farming income is obtained from the following calculations: 1. Production Costs: TC = TFC + TVC and Income:  = TR-TC, TR = Y. Hy. and to determine the level of feasibility of red pepper farming, the R/C ratio analysis is used. The greater the R/C ratio, the farmer is more feasible to run R/C = Acceptance (TR)/Total Cost (TC) criteria: R/C> 1, then farming is profitable; R/C < 1, then farming is not profitable; R/C = 1, then farming is said to be break-even. Based on the results of the study and discussion shows that the income earned by farmers is an average of IDR 9,322.162.50 / MT with an average land area of 0.27 Ha. The R/C ratio obtained from chili farming is 3.99, because of the R/C> 1, this indicates that chili farming is efficient to be cultivated. There are three marketing channels that occur in marketing chili in Wakuli Village to the consumers, which are as follows: Channel I: Farmers® Village collectors? trader ® Large traders? retailers ® Consumers; Channel II: Farmers ® Village collectors ® Retailers ® Consumers and Channel III: Farmers ® Village collectors? trader® Consumers.   Keywords: farming, red pepper, income, feasibility, marketing channels.